Ceria‐Containing Ordered Mesoporous Silica: Synthesis, Properties, and Applications. Issue 2 (23rd November 2015) - Pal, Nabanita; Cho, Eun‐Bum; Patra, Astam K.; Kim, Dukjoon
Abstract: Structural architecture and unique physical, chemical, thermal, and mechanical properties of ordered mesoporous silica materials can be tuned. High flexibility of silica materials can provide good support for different metal nanoparticles, metal oxides, and organic functional groups. The properties of silica materials can vary to a great extent by introducing the optimum amount of metal species co‐doped, dispersed or composites with the silica mesostructure. The present study investigates the deposition of Ce III/IV /CeO2 on the silica surface by using different wet chemical engineering methods, illustrates the syntheses of those ceria–silica or metal doped ceria–silica nanomaterials and offers clear picture of the influence that incorporated ceria concentration has on the properties of the support material. Ceria–silica based ordered mesoporous materials can have numerous applications is also discussed in this article, emphasizing its use as a heterogeneous catalyst in particular. Abstract : Materials for sustainable chemistry : Advanced mesoporous materials are set to be the next generation of catalysts. This contribution discusses the synthesis and functionalization of mesoporous ceria–silica materials and their wide range of catalytic applications in organic synthesis, electrocatalysis, bio‐fuel, environmental cleaning, and photocatalysis.